Crystallization of the secondary alcohol dehydrogenase from: Thermoanaerobacter ethanolicus 39E - Ami, R. K. [UNESP]; Watanabe, L. [UNESP]; Fontes, M. [UNESP]; Burdette, D. S.; Zeikus, J. G. (My University, 1996)
The secondary alcohol dehydrogenase from the thermophile Thermoanaerobacter ethanolicus 39E has been crystallized at 40°C by vapour difussion using polyethelene glycol as a precipitant. The orthorhombic crystals belong to the space group P 21212 with cell constants of a=170.0Å, b=125.7Å and c =80.5Å. A native X-ray diffraction data set has been collected to 2.7Å resolution.